FAKE NEWS IN SINGAPORE: EFFECTS OF PERCEIVED SOURCE CREDIBILITY ON INTENTION TO SHARE NEWS AND JUDGING NEWS ACCURACY IN MODERATED-MEDIATED PATHWAYS INVOLVING BELIEVABILITY, PERSONAL INVOLVEMENT AND MEDIA LITERACY - TAY YU RONG (2018)
Bachelor's